PEMANFAATAN MULTIMEDIA POWER POINT DALAM SISTEM EMBELAJARAN DARING UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI SISTEM EKSKRESI MANUSIA DI KELAS XI SMA YPI DHARMA BUDI SIDAMANIK TAHUN PELAJARAN 2020/2021 - Wandira, Ayu; Wilson Sitopu, Joni (Jurnal Metabio, 2022)
This study aims to determine the differences in student learning outcomes and the magnitude of the differences between online PowerPoint multimedia and conventional methods on the excretory system topic in grade XI of SMA YPI Dharma Budi Sidamanik in the 2020/2021 academic year. The population was 64 students, consisting of two classes. The sample was taken by random assignment, resulting in two classes: a control class (XI-1) with 32 students and an experimental class (XI-2) with 32 students. The control class was treated using conventional methods, and the experimental class was treated using PowerPoint multimedia. Data analysis was performed by finding the mean (X̅ ), standard deviation (S), and hypothesis testing (t-test) at a significance level of α = 0.05. The results showed that the average post-test score for the control class was 88 and the experimental class was 90.12, with a difference in learning outcomes of 2.12. The results of the hypothesis testing (t-test) obtained t count (2.790) > t table (1.99) at a significance level of α = 0.05 and degrees of freedom (df) = 62, therefore Ho is rejected and Ha is accepted, meaning there is a difference in student learning outcomes using conventional methods and the use of PowerPoint multimedia on the online excretory system material for class XI SMA YPI Dharma Budi Sidamanik in the 2020/2021 academic year. It was concluded that there is a difference in student learning outcomes using conventional methods and the use of PowerPoint multimedia on the online excretory system material for class XI SMA YPI Dharma Budi Sidamanik in the 2020/2021 academic year.